Crosscurrents: Urban Environmental Justice Struggles in Twentieth-Century American Literature. - Crawford, Chiyo. (2017)
Abstract: This dissertation joins the conversation on environmentalism from a humanities perspective that is attentive to the struggle for racial, gender, and class equality in environmental policy and planning. Through an analysis of the works of writers from diverse racial backgrounds spanning the twentieth century--including María Cristina Mena (1893-1965), Jayne Cortez (1936- ), Karen Tei Yamashita (1951- ), Mark Nowak (1964- ), and David Treuer (1970- )--I emphasize that literature's role in the environmental movement is to inspire human values are crucial for change.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of English.; Advisor: Elizabeth Ammons.; Committee: Modhumita Roy, Christina Sharpe, and James Engell.; Keywords: American literature, and Environmental studies.